Syllable-based Malay Word Stemmer - Jun, Choi Lee; Mohamad Othman, Rosita; Mohamad , Nurul Zawiyah (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Word stemmer is one of the basic and crucial text processing tools in any languages. Word stemmer is not only useful in morphological study but also play an important role in word level context analysis. Due to the existence of prefix, suffix, infix and a combination of affixes in Malay word, it raises the complexity of performing stemming to Malay word. An approach to stem Malay word using syllabification algorithm is introduced. This approach performs stemming through comparing syllable in the word thus reduces the parsing processes. The approach shows high practicality as it produces a very high accuracy in the evaluation.